The approach focused on practice in preparation of the future teacher as means of improvement of quality of education (Pedagogy of Higher and Secondary Education, 2007)
The article substantiates necessity to use such an approach to training of future teachers which is orientated towards practical application. It is essential as a means to provide high quality cf training in universities' educational process.
Keywords: approach focused on practice; teacher; quality of education